Differential Adjustment Outcomes of International Students at U.S. Universities: Examining the Intersections of Region of Origin, Gender, and Graduate Level - Brunsting, Nelson; Katsumoto, Shinji; Lee, Hyunju; Bingham, W. Patrick (Journal of International Students, 2024)
We present a methodological example of an initial use of critical quantitative analysis (CritQuant) in international education research focused on international students to explore differences in social-emotional experiences intersectionally. Drawing on a sample of 558 international students attending 14 colleges and universities in the United States, we examined students’ belonging, social support, academic stress and confidence, COVID-19 related stress, and social integration by students’ gender, graduate level, and region of origin as well as by combinations of gender, graduate level, and region of origin. Key findings include that graduate and undergraduate female students as well as graduate male students reported better social-emotional experiences compared with undergraduate male students and that students’ region of origin accounted for a range of differences in student outcomes. Findings are discussed in relation to the current literature and with respect to opportunities in the field of international student engagement and global student mobility.